Revisiting the Trapezius Flap as a Reconstructive Option for Cervico-Occipital and Thoracic Spine Regions - Ravikiran Naalla; Vijay Murthy; Shashank Chauhan; Kavya Chinta; Maneesh Singhal (Indian Journal of Plastic Surgery, 2019)
Introduction Reconstruction of complex soft tissue defects around the cervico-occipital and thoracic spine regions is a challenging task. We want to share our experience with trapezius flap for the reconstruction of these complex cases. Materials and Methods A retrospective analysis of patients who underwent reconstruction using trapezius flaps from January 2016 to June 2019 was performed. The indications, technique, complications, and outcomes were analyzed and presented. Results Six patients (three males and three females, >10 years of age) underwent seven reconstructions using trapezius flaps (one of the patients underwent reconstruction using a bilateral trapezius flap). Trapezius flap was used to resurface the parieto-occipital (n = 2), cervico-occipital (n = 2), cervicothoracic (n = 1), and thoracic (n = 1) regions. All flaps showed successful outcomes; one patient had wound dehiscence, and one patient had partial skin graft loss. Conclusion Trapezius flap is a reliable and good alternative to free flaps for the coverage of complex cervical-occipital and upper thoracic soft tissue defects.